Effect of Prenatal Silymarin Administration in the Gestational Period on Fetal Growth - Mahboobeh Gholami (Mashhad University of Medical Sciences, 2017)
Background: Silymarin is a potent inhibitor of apoptosis. The present study aimed to investigate the effect of prenatal silymarin administration during the gestational period on fetal growth. Methods: This experimental study was conducted on 24 virgin female BALB/c mice weighing 20-30 grams. One male animal was caged with two females overnight, and they were examined for the presence of a vaginal plug in the next morning. Presence of vaginal plugs was considered to be gestational day zero (GD0). The mice were randomly divided into four groups, including three groups of pregnant mice administered with silymarin via intraperitoneal injection at doses of 50, 100, and 200 mg/kg/day (groups 1, 2, and 3, respectively) during GD6-15 (organogenesis) and a control group. Animals in the control group received normal saline via the same route in equivalent volumes. Data analysis was performed in SPSS version 18.0, and the pathological scores were compared using Kruskal-Wallis, ANOVA, and Dunn's multiple comparison tests. P-value of less than 0.05 was considered statistically significant. Results: Administration of silymarin had no effect on the weight gain of the mothers. However, placental weight gain decreased in the second and third group compared to the other groups (P≤0.001). In addition, head circumference was observed to reduce in all the treatment groups compared to the control group (P≤0.001). Also, the findings showed significant differences in the resorption rate and weight gain in all the treatment groups compared to the control group (P=0.001). Conclusion: According to the results, silymarin administration during gestation may lower weight gain and decrease placental circumference in the fetus of mice.